2015
DOI: 10.1002/ejic.201501188
|View full text |Cite
|
Sign up to set email alerts
|

Substituent‐Influenced Spin Cross­over in FeIII Quinolylsalicylaldimin­ates

Abstract: The new ligand Hqsal‐4‐OMe was synthesized, and four iron(III) complexes, [Fe(qsal‐4‐OMe)2]Y·CH2Cl2 [Hqsal‐4‐OMe = 4‐methoxy‐N‐(8‐quinolyl)salicylaldimine; Y = ClO4 (1), NO3 (2)] and [Fe(qsal‐4‐OMe)2]Y (Y = PF6 (3), OTf (4)] as well as the isomer [Fe(qsal‐5‐OMe)2]PF6·CH2Cl2 (5), were prepared. UV/Vis spectroscopic studies indicated that the complexes are high‐spin in solution and exhibit a ligand‐to‐metal charge‐transfer band around 400 nm. X‐ray crystallographic studies on [Fe(qsal‐4‐OMe)2]Y·CH2Cl2 (Y = ClO4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…These complexes, although not isolated in the solid state, represent interesting model complexes of the potential spin crossover (SCO) behavior. In order to model the possible electron configurations, both the HS ( S = 5/2, sixtuplet) and LS ( S = 1/2, doublet) configurations were modeled for the three Fe III complexes. The optimized structures of complexes 1c + –3c + show the central ion in a distorted octahedral coordination achieved by the two N1 and N2 atoms and by the O atoms (Figure S8 for 1c + in the HS state).…”
Section: Resultsmentioning
confidence: 99%
“…These complexes, although not isolated in the solid state, represent interesting model complexes of the potential spin crossover (SCO) behavior. In order to model the possible electron configurations, both the HS ( S = 5/2, sixtuplet) and LS ( S = 1/2, doublet) configurations were modeled for the three Fe III complexes. The optimized structures of complexes 1c + –3c + show the central ion in a distorted octahedral coordination achieved by the two N1 and N2 atoms and by the O atoms (Figure S8 for 1c + in the HS state).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the halogen-substituted Hqsal ligands, the MeO-substituted Hqsal ligands have also been explored a lot. Besides the LS complex [Fe­(qsal-3-OMe) 2 ]­PF 6 · n H 2 O, related complexes [Fe­(qsal-5-OMe) 2 ]­Y·sol (Y = Cl – , NCS – , BF 4 – , PF 6 – , BPh 4 – ) with the MeO– group substituted in the 5-position all exhibit SCO, in three cases with hysteresis, while complexes [Fe­(qsal-4-OMe) 2 ]Y (Y = ClO 4 – , NO 3 – , PF 6 – , OTf – ) with substituent in the 4-position are mostly HS complexes with the exception of the OTf – derivative exhibiting a gradual 25% SCO . Magneto-structural analysis revealed that the distortion of the qsal-4-OMe – ligand and intermolecular C–H···O interactions seem to be responsible for the loss of SCO .…”
Section: Introductionmentioning
confidence: 99%
“…Here we apply this approach to the Fe­(III) SCO active metal complex [Fe­(qsal-5-OMe) 2 ]­NCS , and show that this material can be tuned to produce three different spin-switching temperatures, leading to solvatomorphic triple hysteresis and six different stable magnetic states resulting from a single-crystal-to-single-crystal transformation.…”
Section: Introductionmentioning
confidence: 99%